Social innovation within transnational flows of knowledge: The example of student mobility from Bulgaria. Issue 5 (23rd February 2021) - Glorius, Birgit
Abstract: Taking the example of Bulgarians who studied abroad, this paper explores the motives and practices of graduates regarding socially innovative knowledge transfer in order to deliver social benefits for the local community. The paper shows how both stayers and returnees act within a transnational social space, which develops and deepens during and after student mobility. Engaging in socially innovative knowledge transfer is motivated by altruistic stances, by a feeling of loyalty towards the home country and by the desire to lead a meaningful life. The effectiveness of knowledge transfer is related to framing conditions such as local knowledge and the existence of social networks, notably transnational social networks. The results show that the mobility of highly qualified young adults from and to Bulgaria aligns with major European mobility regimes, with an increase of circulatory mobility processes and thus an increase of circulating knowledge and social innovation.